Pengembangan Aplikasi Transliterasi Teks Latin ke Aksara Ulu (Komering) Berbasis Web - Permata Sari, Tia; Novaria Kunang, Yesi (Jurnal PROCESSOR, 2023)
Ulu script is one of the letterforms or writing systems used and developed bt the communities of South Sumatra, specifically the Serawai, Lembak, Rejang, and Pasemah ethnic groups. Typically, Ulu script is used for daily activities such as storytelling, writing poetry, and recording customary laws. Ulu script needs to be preserved because its usage has been declining due to the introduction of the Latin script, which has become the international standard. To preserve Ulu script, a tool is needed to assist in transliterating Latin text into Ulu script. Therefore, this research aims to develop a web-based application for transliterating Latin text to Ulu script using mapping techniques and the sequential search algorithm. The resulting application can assist and facilitate users in transliterating text from Latin to Ulu script.